Comparative effectiveness of treatments for patellofemoral pain: a living systematic review with network meta-analysis. Issue 7 (26th October 2020) - Winters, Marinus; Holden, Sinéad; Lura, Carolina Bryne; Welton, Nicky J; Caldwell, Deborah M; Vicenzino, Bill T; Weir, Adam; Rathleff, Michael Skovdal
Abstract : Objective: To investigate the comparative effectiveness of all treatments for patellofemoral pain (PFP). Design: Living systematic review with network meta-analysis (NMA). Data sources: Sensitive search in seven databases, three grey literature resources and four trial registers. Eligibility criteria: Randomised controlled trials evaluating any treatment for PFP with outcomes 'any improvement', and pain intensity. Data extraction: Two reviewers independently extracted data and assessed risk of bias with Risk of Bias Tool V.2. We used Grading of Recommendations, Assessment, Development and Evaluation to appraise the strength of the evidence. Primary outcome measure: 'Any improvement' measured with a Global Rating of Change Scale. Results: Twenty-two trials (with forty-eight treatment arms) were included, of which approximately 10 (45%) were at high risk of bias for the primary outcome. Most comparisons had a low to very low strength of the evidence. All treatments were better than wait and see for any improvement at 3 months (education (OR 9.6, 95% credible interval (CrI): 2.2 to 48.8); exercise (OR 13.0, 95% CrI: 2.4 to 83.5); education+orthosis (OR 16.5, 95% CrI: 4.9 to 65.8); education+exercise+patellar taping/mobilisations (OR 25.2, 95% CrI: 5.7 to 130.3) and education+exercise+patellar taping/mobilisations+orthosis (OR 38.8, 95% CrI: 7.3 to 236.9)). Education+exercise+patellar taping/mobilisations, with (OR 4.0, 95% CrI: 1.5 to 11.8) or without orthosis (OR 2.6, 95% CrI: 1.7 to 4.2), were superior to education alone. At 12 months, education or education+any combination yielded similar improvement rates. Summary/conclusion: Education combined with a physical treatment (exercise, orthoses or patellar taping/mobilisation) is most likely to be effective at 3 months. At 12 months, education appears comparable to education with a physical treatment. There was insufficient evidence to recommend a specific type of physical treatment over another. All treatments in our NMA were superior to wait and see at 3 months, and we recommend avoiding a wait-and-see approach. PROSPERO registeration number: PROSPERO registration CRD42018079502.